Monaco : Assessment of Financial Sector Supervision and Regulation. (IMF Staff Country Reports; Country Report ;, 2008)
This paper discusses key findings of the assessment of Financial Sector Supervision and Regulation (FSSR) for Monaco. Since the 2002 Offshore Financial Center assessment, the Principality of Monaco has taken important steps to further strengthen an already comprehensive legal framework, supervisory structure, and practices supporting a well-regulated environment. Nonetheless, given Monaco's ambition to develop into a fully-fledged financial center, there is a case for intensifying ongoing efforts to comply with international best practices, in particular regarding the sharing of information with foreign regulatory authorities.